Decision Support System for Prioritizing Road Repairs with Simple Additive Weighting Method - Ramadhan, Bayu Putra; Ardiansyah, Heri; Bianto, Mufti Ari; Saputra, Bagus Dwi; Widodo, Aris (Indonesian Journal of Engineering, Science and Technology, 2025)
The Decision Support System (DSS) is a technology utilized to address the issue of determining road improvement priorities. In this context, DSS will be used to integrate various road assessment criteria and provide recommendations for repair priorities based on proven methods. The aim of this study is to design a decision support system for prioritizing road repairs in Lamongan Regency and to implement this system effectively. The Simple Additive Weighting (SAW) method was chosen for its ability to handle multiple criteria and provide measurable evaluations of alternative solutions. The criteria used in this research include road condition, traffic volume, and socio-economic impact. The results of this system demonstrate a prioritization order for road repairs that can assist in more efficient decision-making, focusing on the most urgent needs. This research is expected to contribute to improving the efficiency of road infrastructure management and to aid authorities in the planning and execution of road repairs. Keywords-- Decision Support System; Road Repair Priority; Simple Additive Weighting.